TATA RUANG AGROFORESTRY LAHAN KAMPUS II POLITEKNIK PERTANIAN NEGERI PAYAKUMBUH JORONG BATU KABAU NAGARI SITANANG - Amrizal Amrizal; Fazlimi Fazlimi; Deswani Panggabean (Politeknik Pertanian Negeri Payakumbuh, 2020)
Land management with an agroforestry system aims to maintain the amount and diversity of land production, so that it has the potential to provide social, economic and environmental benefits (Senoadji, 2012). In the concept of agroforestry spatial planning on campus land II Payakumbuh State Agricultural Polytechnic is quite possible to be implemented by collaborating between current agricultural activities with standing trees (forests) that are beneficial to ecology and sustainability, comforting the surrounding environment. From the results of the study obtained five plant and fisheries species composition in the land of Campus II Payakumbuh State Agricultural Polytechnic, namely estate crops (rubber, sugar cane), fruit trees (guava, matoa, mango, orange), food plants (lowland rice) ), fodder grass (elephant grass) and fisheries (tilapia, tilapia fish and carp). Two agroforestry systems that can be applied for soil and water conservation on the land of Campus II Payakumbuh State Agricultural Polytechnic, namely Agrisilvikultur and Agrosilvofishery, which are respectively: 62,770 M ^ 2 and 12,128 M ^ 2.